CULTURAL TERMS IN THE OLD MAN AND THE SEA AND THEIR TRANSLATIONS INTO INDONESIAN - , FITRI NURANI, Drs. Tofan Dwi Hardjanto, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research attempts to identify and categorize the cultural terms found in the novel The Old Man and the Sea and examine how these cultural terms are translated into Indonesian in Lelaki Tua dan Laut. The data were taken from these two novels. The results of this research show that 297 cultural terms were found. They were classified into five categories: ecology